2022
DOI: 10.3390/agriculture12071012
|View full text |Cite
|
Sign up to set email alerts
|

Key Region Extraction and Body Dimension Measurement of Beef Cattle Using 3D Point Clouds

Abstract: Body dimensions are key indicators for the beef cattle fattening and breeding process. On-animal measurement is relatively inefficient, and can induce severe stress responses among beef cattle and pose a risk for operators, thereby impacting the cattle’s growth rate and wellbeing. To address the above issues, a highly efficient and automatic method was developed to measure beef cattle’s body dimensions, including the oblique length, height, width, abdominal girth, and chest girth, based on the reconstructed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…While this method is straightforward, its limitation lies in the fact that only one side of the cattle body is captured in the acquired point cloud data. Li et al (2022) [ 66 ] developed a fully automated method for measuring beef cattle’s body dimensions. This approach not only achieved a high accuracy and speed in measurement but also covered a comprehensive set of measurement locations, making it a practical solution for cattle body measurement with significant commercial potential.…”
Section: Livestock Body Measurement Sensing Data Analysismentioning
confidence: 99%
“…While this method is straightforward, its limitation lies in the fact that only one side of the cattle body is captured in the acquired point cloud data. Li et al (2022) [ 66 ] developed a fully automated method for measuring beef cattle’s body dimensions. This approach not only achieved a high accuracy and speed in measurement but also covered a comprehensive set of measurement locations, making it a practical solution for cattle body measurement with significant commercial potential.…”
Section: Livestock Body Measurement Sensing Data Analysismentioning
confidence: 99%
“…Tests on farm conditions reported an accuracy as high as 91.6% on weight measurements based on the proposed model. Furthermore, a highly efficient and automatic method was developed by Li et al [12] to measure beef cattle's body dimensions based on the reconstructed three-dimensional point cloud. The results showed that the errors of calculated body dimensions, i.e., the oblique length, height, width, abdominal girth, and chest girth, were always lower than 3%.…”
mentioning
confidence: 99%